2021
DOI: 10.1017/jfm.2021.977
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and length scales in vertical convection of liquid metals

Abstract: Using complementary experiments and direct numerical simulations, we study turbulent thermal convection of a liquid metal (Prandtl number $\textit {Pr}\approx 0.03$ ) in a box-shaped container, where two opposite square sidewalls are heated/cooled. The global response characteristics like the Nusselt number ${\textit {Nu}}$ and the Reynolds number $\textit {Re}$ collapse if the side height $L$ is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…Due to rotational symmetry, most experiments and many numerical investigations have been conducted in upright cylinders, hence the aspect ratio Γ = D/H between cylinder diameter D = 2R and height H is a parameter quantifying the geometrical constraints. The height H is a good length scale in RBC only for sufficiently large Γ because only then is Nu independent of Γ (Ahlers et al 2022;Zwirner et al 2021). Nevertheless, most experiments are conducted in cylinders of Γ close to 1 in order to maximize H, and in this way Ra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to rotational symmetry, most experiments and many numerical investigations have been conducted in upright cylinders, hence the aspect ratio Γ = D/H between cylinder diameter D = 2R and height H is a parameter quantifying the geometrical constraints. The height H is a good length scale in RBC only for sufficiently large Γ because only then is Nu independent of Γ (Ahlers et al 2022;Zwirner et al 2021). Nevertheless, most experiments are conducted in cylinders of Γ close to 1 in order to maximize H, and in this way Ra.…”
Section: Introductionmentioning
confidence: 99%
“…2022; Zwirner et al. 2021). Nevertheless, most experiments are conducted in cylinders of close to 1 in order to maximize , and in this way .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is recognised widely that the mean velocity profile in wall shear flows cannot be applied to describe vertical convection (VC), due to the effect of buoyancy (Ke et al 2020). The VC is the buoyancy-driven flow along a vertical heated wall, and it usually includes three configurations (Hölling & Herwig 2005;Howland et al 2022): (a) a single heated vertical plate immersed in an ambient fluid (Tsuji & Nagano 1988a,b;Wells & Worster 2008;Ke et al 2020), abbreviated as 'plate VC' hereafter; (b) a closed cavity with two opposite sidewalls heated at different temperatures (Shishkina 2016;Jiang et al 2019;Wang et al 2021;Zwirner et al 2022), abbreviated as 'cavity VC' hereafter; (c) a vertical infinite channel with periodic boundary conditions in the wall-parallel directions (Pallares et al 2010;Ng et al 2013Ng et al , 2015Howland et al 2022;Ching 2023), abbreviated as 'channel VC' hereafter. This study focuses on the last configuration of VC, as shown in figure 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…2021; Zwirner et al. 2022), abbreviated as ‘cavity VC’ hereafter; ( c ) a vertical infinite channel with periodic boundary conditions in the wall-parallel directions (Pallares et al. 2010; Ng et al.…”
Section: Introductionmentioning
confidence: 99%
“…The work devoted to the study of natural convection in liquid gallium for the crystal growth applications can be distinguished as one of the early ones [20]. In some studies on inclined convection, the position of a cylindrical container at the extreme horizontal point will also correspond to the case of vertical convection [8,9] The most complete study from the fluid mechanics point of view on vertical convection of liquid metal in a box-shaped container was published in [21].…”
Section: Introductionmentioning
confidence: 99%